Self-medication in children and adolescents - Pereira, Francis S. V. T.; Bucaretchi, Fabio; Stephan, Celso [UNESP]; Cordeiro, Ricardo (Sociedade Brasileira de Pediatria, 2007)
Objective: To determine the prevalence of self-medication in children and adolescents in the municipalities of Limeira and Piracicaba, state of S (a) over tildeo Paulo, and to correlate results with sociodemographic indicators and with the use of health care services (public or private).Methods: Descriptive population-based study of a simple random sample from the two municipalities, comprised of 772 inhabitants from 85 urban census sectors selected through cluster sampling. Inclusion criteria: age <= 18 years; interview with one parent/tutor; consumption of at least one drug in the previous 15 days. Subjects were divided into two study groups according to their pattern of drug use: self-medication (lay advice) and medical prescription. Linear association tests, descriptive analysis of variables and multiple logistic regression tests were carried out to analyze data.Results: the prevalence of self-medication was 56.6%. Mothers (51%) and drugstore employees (20.1%) were most frequently responsible for self-medication. The main groups of self-prescribed drugs were: analgesic/antipyretic and non-hormonal anti-inflammatory drugs (52.9%); drugs acting on the respiratory tract (15.4%) and gastrointestinal drugs (9.6%); and systemic antibiotics (8.6%). The situation that most commonly motivated self-medication were respiratory diseases (17.2%), fever (15%), and headache (14%). Subjects in the age group of 7-18 years (odds ratio = 2.81) and public health care users (odds ratio = 1.52) showed increased risk for self-medication.Conclusions: the prevalence of self-medication in children and adolescents was high, which reinforces the need for public health interventions aiming at preventing this practice.